Linking School Culture to Successful Curriculum Reform - Marina Grgić; Michelle Jutzi (Education Sciences, 2024)
This study focused on the connection between organisational school culture and the success of curriculum reform. Utilizing a sample of 348 teachers in 25 Swiss schools, we investigated how different school culture types correlate with teachers’ perceived success of the current process of implementing the “Media and Information Literacy” curriculum. We found that the school culture type Clan is the most dominant across the schools and found a negative connection between the school culture type Hierarchy and teachers’ perceived reform success. An exploratory cluster analysis was used to identify further profiles of school culture that were not based on the dominant culture but were determined based on the distribution of mean values. Two other profiles were identified in a further procedure: Collegial Associates and Competitive Organisations. These results thus fill a gap in the previous research on school culture that had particularly set out to identify the dominant school culture. Based on the results, we cannot only confirm the validity of the Organisational Culture Assessment Instrument for Swiss schools but also give indications as to which characteristics of school culture types are hindering the perceived success of curriculum reforms from the teachers’ points of view.